Pediatric Logistic Organ Dysfunction (PELOD) Score as prognosis of multiple organ failure in sepsis - Hendra Hendra; Ari Lukas Runtunuwu; Jeanette Irene Chistie Manoppo (Paediatrica Indonesiana, 2010)
Background Sepsis is an emergency event that often found inpediatric intensive care unit. If this condition is not early detectedand promptly treated, severe complications including septic shockand multiple organ failure may result that can end up as death.Objective To discover alternative measurement as a prognosis ofmultiple organ failure in sepsis.Methods This cross sectional study was conducted in 37 patientsdiagnosed as sepsis. The age of the patients were 1 month until 13years and the patients were hospitalized in child health departmentof R. D. Kandou Hospital during June 2009 – September 2009.Result Bronchopneumonia (18) was the most commoninfection source, followed by gastroenteritis (11), encephalitis(6) and meningitis (2). The bacteria which is found was Proteusmirabilis (5), Citrobacter difersus (5), Staphylococcus aureus (3),Escherichia coli (2) and Acinetobacter baumannii (1). There wasno significant difference in gender distribution, nutrition statusand blood culture between both groups. Laboratory findings andclinical manifestations which included white blood cell (WBC)> 10.000/μL (34), platelet count > 150.000 (27) and bodytemperature 38oC – 39oC (20). There was a correlation betweenPELOD score and multiple organ failure (P=0.02). A higherPELOD score will increase opportunity to get multiple organfailure. In patient with organ failure more than two, PELODscore 0-10 (9 patients), score 11-20 (7 patients), score 21-30 (8patients), and score 31-40 (1 patient).Conclusion There was a correlation between PELOD score andmultiple organ failure in patient with sepsis. A higher PELODscore will increase opportunity to get multiple organ failure.